2021
DOI: 10.1017/s1368980021004006
|View full text |Cite
|
Sign up to set email alerts
|

Costing recommended (healthy) and current (unhealthy) diets in urban and inner regional areas of Australia using remote price collection methods

Abstract: Objective: To compare the cost and affordability of two fortnightly diets (representing the national guidelines and current consumption) across areas containing Australia’s major supermarkets. Design: The Healthy Diets Australian Standardised Affordability and Pricing protocol was used. Setting: Price data were collected online and via phone calls in 51 urban and inner regional locations across Australia. Participants: N/A. Results: H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 32 publications
1
10
0
Order By: Relevance
“…The influence of such factors might explain why households in Greater Brisbane continue to purchase the current diet despite the recommended diet being 19% less expensive. This corresponds to findings of prior research using the Healthy Diets ASAP protocol in Australia that has shown that, under current policy settings, which include the exemption of "basic, healthy foods" from the Goods and Services Tax (GST) [9,10], the current diet is from 14% to 23% more expensive than the recommended diet in Brisbane [11,12], Canberra and Sydney [10], regional Victoria [13], Aboriginal communities in remote Australia [8] and in two large supermarket chains nationally [14].…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…The influence of such factors might explain why households in Greater Brisbane continue to purchase the current diet despite the recommended diet being 19% less expensive. This corresponds to findings of prior research using the Healthy Diets ASAP protocol in Australia that has shown that, under current policy settings, which include the exemption of "basic, healthy foods" from the Goods and Services Tax (GST) [9,10], the current diet is from 14% to 23% more expensive than the recommended diet in Brisbane [11,12], Canberra and Sydney [10], regional Victoria [13], Aboriginal communities in remote Australia [8] and in two large supermarket chains nationally [14].…”
Section: Discussionsupporting
confidence: 78%
“…The protocol comprises five sections: standardised current (unhealthy) and recommended (healthy, equitable and more sustainable) diet pricing tools; store location and sampling; calculation of household incomes; food price data collection; and analysis and reporting [11]. The protocol has been described in detail elsewhere [11] and applied in multiple studies [8][9][10][11][12][13][14].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Lessons one and three explicitly demonstrate this idea – challenging the inadequate policy efforts of non-health sectors to engage in and address key determinants of food insecurity until the COVID-19 pandemic in Australia. Lesson two subsequently challenges Australia’s inadequate policy focus on comprehensively addressing the unaffordability of healthy diets for low-income households (an issue that has been quantified previously (Zorbas et al, 2022 ) but that the pandemic has thrown into the spotlight). Finally, we argue that the COVID-19 specific policy response demonstrated the recognised responsibility of governments for addressing food insecurity – including by driving appropriate policy and public rhetoric that reflects lived experiences of the social determinants of disadvantage and enables long-term, structural policy progress (Backholer et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…While some studies have suggested that a healthy diet is not more expensive than less healthy options [ 6 , 7 ], this report estimated that the price of a healthy diet (rich in whole grains, fruits, vegetables, legumes, nuts and seeds, and dairy products) costs 60% more than diets that only met essential nutrient requirements based on a limited number of foods. It also estimated that 3 billion people could not afford the cost of a healthy diet, without taking into account recent global events such as the SARS-CoV-2 pandemic that severely impacted employment and household incomes [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%